2016
DOI: 10.31899/rh8.1012
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a community-based SGBV prevention model in emergency settings in Uganda: Testing the 'Zero Tolerance Village Alliance' intervention

Abstract: Population Council 1 ; Lutheran World Federation 2 ; Thohoyandou Victim Empowerment Programme 3; Child Health & Development Centre 4 ; Refugees Department, Office of the Prime Minister, Uganda 5 UNHCR Regional Services Centre 6 The Population Council confronts critical health and development issues-from stopping the spread of HIV to improving reproductive health and ensuring that young people lead full and productive lives. Through biomedical, social science, and public health research in 50 countries, we work… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
2

Year Published

2018
2018
2018
2018

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 2 publications
0
2
0
2
Order By: Relevance
“…The data for this paper come from a cross-sectional baseline survey that was aimed at generating evidence to inform a community-based intervention to prevent SGBV in an emergency context in Uganda. A detailed study and intervention design may be found elsewhere [ 30 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The data for this paper come from a cross-sectional baseline survey that was aimed at generating evidence to inform a community-based intervention to prevent SGBV in an emergency context in Uganda. A detailed study and intervention design may be found elsewhere [ 30 ].…”
Section: Methodsmentioning
confidence: 99%
“…SGBV is a challenge in the settlement area. In a community baseline survey carried out in the study site in 2015, a large proportion of female household heads reported experiencing physical IPV (69%) and sexual IPV (63%) since moving into the settlement area—the majority (68%) had lived in the area for more than 2 years [ 30 ]. Furthermore, many female heads of household indicated that they had experienced non-partner physical violence (47%) and non-partner sexual violence (46%) since they started residing in the settlement.…”
Section: Methodsmentioning
confidence: 99%
“…En l'absence d'un cadre clair de responsabilisation et de suivi pour la SSR (y compris la planification familiale) pendant les crises humanitaires, les données disponibles proviennent d'études spécifiques. La rareté des données montre qu'il est nécessaire de recourir davantage à la contraception d'urgence pour atténuer la grossesse liée au viol (7). En outre, lorsque des services de planification familiale sont disponibles et accessibles, l'utilisation de la planification familiale par les femmes augmente (13).…”
Section: Défis Et Enseignements Tirésunclassified
“…Avec la perturbation des services de protection, la violence sexuelle augmente souvent pendant les situations d'urgence pour toucher environ 1 femme sur 5 (6), aggravant les menaces qui pèsent sur la santé et la survie des femmes et des filles. La situation est encore aggravée par le manque d'accès à la contraception d'urgence (7), comme l'a souligné un récent examen du Groupe de travail inter-organisations sur la santé en matière de reproduction des réfugiés (8). En outre, 12 des 13 pays ayant la plus faible prévalence de la contraception moderne en 2016 sont des « États fragiles » (9).…”
unclassified